Droplet Collision Simulation by a Multi-Speed Lattice Boltzmann Method (Communications in Computational Physics, 2020)
Realization of the Shan-Chen multiphase flow lattice Boltzmann model isconsidered in the framework of the higher-order Galilean invariant lattices. The presentmultiphase lattice Boltzmann model is used in two-dimensional simulation of dropletcollisions at high Weber numbers. Results are found to be in a good agreement withexperimental findings.